Implementasi Manajemen Kesiswaan dalam Meningkatkan Prestasi Siswa MA Unggulan Mamba’ul Huda Krasak Tegalsari Banyuwangi - Moh. Harun Al Rosid; Istiqomah Istiqomah (Institut Agama Islam Darussalam Blokagung, 2020)
The objectives of this study were: (1) To determine the implementation of student management at MA Unggulan Mamba'ul Huda Krasak Tegalsari for the 2019/2020 Academic Year; (2) To determine the achievements of MA Featured students Mamba'ul Huda Krasak Tegalsari for the 2019/2020 academic year; (3) To find out the inhibiting factors and supporting factors of student management in improving the achievements of MA MA Mamba'ul Huda Krasak Tegalsari 2019/2020 Academic Year. In this research, using a qualitative descriptive method with data collection techniques using observation, interviews, and also documentation. Data analysis using analysis: (1) data reduction, (2) presentation of data, and (3) drawing conclusions and validity used is data triangulation. The results of this study indicate that: (1) Planning for new student admissions is done one year earlier; (2) New student orientation is held for 3 days; (3) Implementation of student disciplinary coaching involves BP / BK and coordinator of extracurricular activities; (4) Development of intracuricular activities (academic) is done by providing additional lessons; (5) coaching for extracurricular (non-academic) activities is carried out through developing interest talents. In general, the academic achievement of MA Unggul Mamba'ul Huda Krasak Tegalsari students from year to year continues to increase, in the semester examinations there are no students who do not advance the grade. At the time of the National Examination there were no students who did not pass. Supporting factors for student management in improving student achievement include: 1) adequate educational facilities and infrastructure; 2) High student enthusiasm for learning; 3) professional educators; 4) Educators and education personnel come from Islamic boarding schools. Meanwhile, the inhibiting factors are: 1) sharing of learning time with time in dormitories; 2) lack of student discipline